Opportunities Amidst Uncertainties China–EU Security Cooperation in the context of the ‘One Belt One Road’ initiative - Hongfei, Gu (Overcoming Controversies in East Asia, 2017)
How does China seek security cooperation on the vast Eurasian continent? For China, this geopolitical border is becoming more and more important. A new generation of Chinese leaders put forward the ‘One Belt, One Road’ (OBOR) Initiative for the Eurasian continent has brought new opportunities for cooperation, but it also brings new security challenges. Is it possible for Europe to have more security cooperation and interaction with China? As an important power worldwide, China and the European Union (EU) could share common interests in maintaining international and regional peace and stability. As the security challenges are becoming increasingly complex and transnational, the EU and China will assume more responsibility for peace and security matters. This paper aims to have a general, yet strategic assessment of China’s security cooperation towards the European Union. It starts with a brief overview of China–EU security cooperation during the past decade, then analyze the opportunities and challenges of China and the EU’s security cooperation in the context of OBOR Initiative, and put forward some feasible suggestions for the future cooperation.